ABOUT THE APPLICATION OF THE "TANGLED LOGICAL CHAIN" METHOD IN CLASSROOM ACTIVITIES - Mahmudov Zokirjon Sotivoldiyevich; Xodjibayev Vali Raximdjanovich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
The article examines the confused logical chain method, which is used in order to increase the activity of students in higher mathematics in classes and to evaluate their knowledge level fairly and quickly. It is thought that the method can be used for a separate subject, section and whole part of Higher Mathematics.